Reliability and modality analysis of patellar height measurement in pediatric knee - Kwak, Yoon Hae; Park, Soo-Sung; Huser, Aaron J.; Kim, Keunho; Koh, Yong-Gon; Nam, Ji-Hoon; Kang, Kyoung-Tak (Frontiers in Pediatrics, 2024)
Introduction Various measurement methods and imaging technique are in use to measure patellar height in pediatric patients. However, there is no gold standard as to which measurement method and modality are the most reliable for pediatric patients. Therefore, the aim of this study was to determine the inter-observer reliability, intra-observer reliability, and applicability of various patellar height measurement methods in pediatric knee. Additionaly, we analyzed the reliability across different imaging modalities. Methods Total 450 pediatric patients (age: 5-18 years) were evaluated using lateral knee radiographs and magnetic resonance imaging (MRI). The patellar height ratios were measured using five methods. Five methods were Insall–Salvati (IS), Koshino–Sugimoto (KS), Blackburne–Peel (BP), modified Insall–Salvati (MIS), and Caton– Deschamps (CD). The patients were categorized into two age groups: P (ages 5-13) and Q (ages 14-18). Each measurement was conducted twice by two raters. The intra-observer reliability, inter-observer reliability and inter-modality reliability were calculated. In addition, applicability was defined as the possibility to apply each measurement method to each age group. Results The KS method showed the highest inter-observer reliability and intra-observer reliability when using MRI for both age groups. The inter-observer reliability and intra-observer reliability of the IS for lateral knee radiographs was highest among all observers for group Q. The CD method showed the highest inter-observer reliability in group P, while the KS showed the highest intra-observer reliability in group P using lateral radiographs. The KS method showed the highest inter-modality reliability in group P, while the IS showed the highest inter-modality reliability in group Q. The KS method was applicable to all patients when using lateral knee radiography, and the IS method was applicable to all patients when using MRI. Conclusions Our results show that the reliability of various measurement method and imaging technique differed based on pediatric knee age group when measuring patellar height. Therefore, in the case of pediatric patients, reliability measurement methods and imaging techniques according to the patient's age should be applied.